Detection of Bacteria Causes Ventilator Associated Pneumonia with Bronchoalveolar Lavage Culture and Endotracheal Aspirate Culture - Hairiah Asty; Loesnihari R; Syarani F (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Ventilator associated pneumonia (VAP) is the most common hospital infection in ICU. Proper and prompt diagnosis and treatment with adequate antibiotics can reduce the high mortality rate, and prevent complications and antibiotic resistance. Invasive methods, such as bronchoalveolar lavage can make a more accurate diagnosis and help with the choice of antibiotics, but require lung experts. While non-invasive methods, such as endotracheal aspirate can be done faster with less complications. The aim of the study was to determine the pattern of bacterial and bacterial sensitivity to bronchoalveolar lavage and endotracheal fluid. This was an observational study with cross-sectional approaches performed at the Intensive Care Unit of RSUP H. Adam Malik Medan, in August 2017 - February 2018. The sample of  23 patients  who met the criteria and was suspected with VAP was carried out by taking endotracheal aspirate and bronchoalveolar lavage. The samples obtained were culture and sensitivity test using BD Phoenix. There was bacteria pattern had compatibility at moderate levels and there was sensitivity and antibiotic resistance were not significantly different from bronchoalveolar cultures and endotracheal aspirate cultures. Endotracheal aspirate culture has a sensitivity of 78.9% and a specificity of  75% for diagnose VAP. Information on the identification of bacteria and sensitivity testing in patients with suspected VAP is required using appropriate sampling techniques. There were no significant differences between bronchoalveolar lavage culture and endotracheal aspirate culture to diagnosing VAP. Endotracheal aspirate culture is a non invasive diagnostic tool that can be used as an alternative diagnostic tool in patients with suspected VAP.